Sbeik Thom at the Season of Cambodia Festival: Performing Memory after the Killing Fields in a Post-9/11 New York City1. Issue 1 (11th February 2016) - GOODLANDER, JENNIFER
Abstract : During the period of the Khmer Rouge (1975–9) culture was turned back to 'Year Zero' through the murder and destruction of about 90 per cent of the country's artists and intellectuals. These art forms are now being remembered, revised and reinvented in order to articulate a contemporary Cambodian identity. In the spring of 2013, New York City hosted a month-long festival of Cambodian arts called the Season of Cambodia. The festival, which sought to celebrate and reaffirm Cambodian identity through the arts, set the stage for other post-conflict nations seeking renewal through artistic expression. A performance of sbeik thom, or large shadow puppets, was staged at the site of the former World Financial Center, seeking to create a dialogue between New York and Cambodia themed around healing and renewal.